Design Strategies of Unmanned Aerial Vehicle-Aided Communication for Disaster Recovery - Tuna, Gurkan; Mumcu, Tarik Veli; Gulez, Kayhan (IEEE, 2012)
This paper presents a novel approach of using unmanned aerial vehicles (UAVs) to establish a communication infrastructure in case of disasters. Due to the collapse of buildings, power systems, and antennas, the collapse of communication infrastructure is the usual effect of disasters. In this study, we propose an emergency communications system established by unmanned aerial vehicles (UAVs). The system is a post-disaster solution; hence, it can be used anywhere required. In this study, first we briefly explain the details of the system in three aspects: end-to-end communication, localization and navigation, and coordination Then, we evaluate the efficiency of the localization and navigation subsystem. Our simulation studies with Air Robot quadrotor helicopters in Unified System for Automation and Robot Simulation (USARSim) simulation environment show that UAV-aided communications system can be used in case of disasters to establish an emergency communications infrastructure in terms of localization and navigation.
Keywords: Unmanned aerial vehicles; post-disaster communications; disaster recovery; navigation and localization; Engineering; Optics